Designing and elucidation of a social entrepreneurship model in the field of health - Mooghali, Alireza; Kazemi, Bahador (Researcher Bulletin of Medical Sciences, 2020)
The aim of this study was to design and explain a social entrepreneurship model in the field of health. In the present descriptive-correlational study, the statistical population of the qualitative section of the health and health sector experts consisted of all the employees of the health area. The qualitative sampling was purposeful judgments. The sampling of a small, simple random sample with Morgan's table consisted of 290 health workers. In order to collect data, Delphi method was used in qualitative section and a questionnaire was used in the quantitative section. Descriptive statistics (means, standard deviations, frequencies and percentages) and inferential methods (Pearson’s correlation coefficient and factor analysis) were used to analyse data. SPSS 16.0 and Amos 8.5 software programs were used. The results of this research indicated that different aspects of financing, promoting entrepreneurship level awareness and identifying entrepreneurship opportunities have a positive and significant effect on social entrepreneurship in the field of health. In conclusion, by enhancing and appropriate financing arrangements, one can promote the level of entrepreneurial consciousness and identify entrepreneurial opportunities that are in fact the gate to enter entrepreneurship